Jesuit survival and restoration: a global history, 1773-1900 - Maryks, Robert A.; Wright, Jonathan (Studies in the history of Christian traditions 1573-5664, 2014)
Jesuit Survival and Restoration offers a global account of the Society of Jesus's history during the post-Suppression and post-Restoration eras